Influence of Dimensionality on the Charge Density Wave Phase of 2H‐TaSe2. Issue 6 (30th March 2022) - Chowdhury, Sugata; Rigosi, Albert F.; Hill, Heather M.; Briggs, Andrew; Newell, David B.; Berger, Helmuth; Hight Walker, Angela R.; Tavazza, Francesca
Abstract: Metallic transition metal dichalcogenides like tantalum diselenide (TaSe2 ) exhibit exciting behaviors at low temperatures, including the emergence of charge density wave (CDW) states. In this work, density functional theory (DFT) is used to catalog influences of van der Waals interactions and reduced dimensionality on the CDW atomic structures as a function of thickness, with the former effect being most strongly present between the layers of bulk TaSe2, slightly reduced in few‐layer TaSe2, and effectively absent in monolayer (1L) TaSe2 . To support the validity of the DFT models, experimental Raman data are provided for monolayer, bilayer, and bulk TaSe2 in the spectral range 165–215 cm −1 . The phonons seen in the experimental Raman spectra are compared with the results calculated from the DFT models as a function of temperature and layer number. The matching of data and calculations substantiates the model's description of the CDW structural formation as a function of thickness, which is shown in depth for 1L through 6L systems. These results highlight the importance of understanding interlayer interactions, which are pervasive in many quantum phenomena involving 2D confinement. Abstract : Density functional theory is used to catalog influences of van der Waals interactions and reduced dimensionality on atomic structures of single‐ and multilayer TaSe2 at both room temperature and below the charge density wave critical temperature. These results highlight the importance of understanding interlayer interactions that are pervasive in many quantum phenomena involving 2D confinement.